Efficacy and safety of radiofrequency ablation for primary and secondary hyperparathyroidism with or without previous parathyroidectomy: a retrospective study. (31st December 2022) - Chen, Chi-Cheng; Chen, Hsiu-Ling; Chiang, Pi-Ling; Luo, Sheng-Dean; Chang, Yen-Hsiang; Chen, Wei-Chih; Wang, Cheng-Kang; Lin, An-Ni; Chen, Yueh-Sheng; Chi, Shun-Yu; Lin, Wei-Che
Abstract: Introduction: This study aimed to investigate and compare the therapeutic efficacy and safety of ultrasound-guided radiofrequency ablation (RFA), between primary hyperparathyroidism (PHPT) and secondary hyperparathyroidism (SHPT) patients, with or without previous parathyroidectomy (PTX). Subjects and Methods: A total of 21 patients (7 PHPT, 14 SHPT) underwent RFA for hyperparathyroidism (HPT) at Kaohsiung Chang Gung Memorial Hospital, Taiwan. Five of the 14 SHPT patients had previously received PTX. The laboratory data, volume change of each parathyroid nodule, symptomatic scores, and complications were analyzed and compared between all groups at 1 and 7 days, and at 1, 3, 6, and 12 months after RFA. Results: After RFA, the volume reduction ratio (VRR) for all patients at the last follow-up was 93.76%, and clinical symptoms significantly improved. At 12 months, all PHPT patients achieved successful treatment of intact PTH (iPTH). In SHPT patients, the mean iPTH value significantly decreased 1-day post-RFA, subsequently exhibiting a transient rebound which proceeded to decrease, with 57.1% reaching successful treatment standards. SHPT patients with PTX showed a lower complication score, shorter ablation time, higher iPTH baseline and outcomes, and lower VRR, compared to patients without PTX. The serum calcium level significantly decreased to normal range in 85.7% of all patients at 12 months. Severe hypocalcemia occurred in 23.8% at 1 week, and all were corrected with calcium supplements. Conclusions: RFA demonstrates a therapeutic efficacy similar to PTX. It can thus be considered an effective alternative treatment for PHPT, SHPT, or post-PTX patients who are unsuitable for another PTX.